Gradenigo’s syndrome secondary to chronic otitis media on a background of previous radical mastoidectomy: a case report - Plodpai, Yuvatiya (BioMed Central, 2014)
INTRODUCTION: Gradenigo’s syndrome is nowadays a rare condition characterized by a triad of otorrhea, facial pain with trigeminal nerve involvement and abducens nerve palsy. Most cases are caused by medial extension of acute otitis media into a pneumatized petrous apex and surgical drainage is usually the treatment of choice. We present a case highlighting the pathological mechanism of this disease, demonstrate rare radiological findings associated with this patient, and showcase successful medical treatment without surgical intervention. CASE PRESENTATION: A 63-year-old Thai man presented with complete Gradenigo triad as a complication of chronic otomastoiditis in spite of clinical history of previous radical mastoidectomy and a nonpneumatization of the petrous apex. Magnetic resonance imaging showed abnormal prominent enhancement at the roof of his right temporal bone, and the dura overlying the floor of right middle cranial fossa and right cavernous sinus. Magnetic resonance imaging also detected right petrous apicitis. With the use of intravenous antibiotics and topical antibiotic eardrops, recovery was observed within 5 days with complete resolution within 2 months. CONCLUSIONS: Although there is little evidence to support the use of medical therapy in the treatment of Gradenigo’s syndrome resulting from chronic ear disease, we here demonstrate successful conservative treatment of Gradenigo’s syndrome following chronic otitis media in a patient who underwent previous radical mastoidectomy.